A Meta-analysis on the Outcome of Sequential Glaucoma Drainage Implantation. Issue 3 (March 2020) - Yoon, Dan; Vajaranant, Thasarat
Abstract : Precis: A meta-analysis shows that second glaucoma drainage implantation can be effective after a failed drainage implant. There is a need for continued glaucoma medications and the risk of corneal decompensation. Purpose: Studies on second glaucoma drainage implantation are small and exploratory. We performed a meta-analysis on the efficacy of second glaucoma drainage implantation. Materials and Methods: The intraocular pressure (IOP) and the number of glaucoma medications were compared preoperative to postoperative after second drainage implantation. Kaplan-Meier survival curves were aggregated and compared with the survival curve from the Tube versus Trabeculectomy study. Results: Nine studies, all retrospective, were included in the meta-analysis. Our results showed that second drainage implantation significantly lowered the IOP and reduced the number of medications. Most patients still required medications for adequate IOP control. Second drainage implants tended to fail earlier than first drainage implants in the Tube versus Trabeculectomy study. The most common complication after second drainage implants was corneal decompensation. Conclusions: Second glaucoma drainage implantation can be considered a viable approach after a failed drainage implant, but patients should be counseled on the need for continued medical therapy and the risk of corneal decompensation.